Multiple criteria assessment of a new tram line development scenario in Vilnius City public transport system - Jakimavičius, Marius; Burinskienė, Marija (Transport, 2013)
This paper considers the technological development of an additional network for Vilnius City public transport. Several types of scenarios for the development of Vilnius City tram line were analysed. This paper describes the situation pertaining to Vilnius City transport system as well as the traffic parameters, which are used for a multiple attribute ranking of a tram line development in Vilnius City. The multiple attribute criteria methods have been chosen to perform the ranking of three development scenarios and to estimate the best alternative based on the traffic conditions of Vilnius City. The experts of different decision-making groups have performed the importance analysis of traffic parameters, which were chosen for the assessment of alternative scenarios for the tram line development. The transport system experts were used to determine the relative weights of indicators. Two methods – TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) and SAW (Simple Additive Weighting) – were used and compared to determine the best transport development alternative based on traffic parameters. Two multi-criteria methods were applied in this research to perform the ranking of more accurate alternatives and to make the comparison of calculation results.First Published Online: 24 Dec 2013